Differential Adaptive Responses of Staphylococcus aureus to In Vitro Selection with Different Antimicrobial Peptides - Shireen, Tahsina (American Society for Microbiology, 2013)
We subjected Staphylococcus aureus ATCC 29213 to serial passage in the presence of subinhibitory concentrations of magainin 2 and gramicidin D for several hundred generations. We obtained S. aureus strains with induced resistance to magainin 2 (strain 55MG) and gramicidin D (strain 55GR) that showed different phenotypic changes in membrane properties. Both exhibited a change in membrane phospholipid content and an increase in membrane rigidity, while an alteration in net charge compared to that of the control occurred only in the case of 55MG.